SOX2 protein biochemistry in stemness, reprogramming, and cancer: the PI3K/AKT/SOX2 axis and beyond - Schaefer, Thorsten (Oncogene, 2019)
Research of the past view years expanded our understanding of the various physiological functions the cell-fate determining transcription factor SOX2 exerts in ontogenesis, reprogramming, and cancer. However, while scientific reports featuring novel and exciting aspects of SOX2-driven biology are published in near weekly routine, investigations in the underlying protein-biochemical processes that transiently tailor SOX2 activity to situational demand are underrepresented and have not yet been comprehensively summarized. Largely unrecognizable to modern array or sequencing-based technology, various protein secondary modifications and concomitant function modulations have been reported for SOX2. The chemical modifications imposed onto SOX2 are inherently heterogeneous, comprising singular or clustered events of phosphorylation, methylation, acetylation, ubiquitination, SUMOylation, PARPylation, and O-glycosylation that reciprocally affect each other and critically impact SOX2 functionality, often in a tissue and species-specific manner. One recurring regulatory principle though is the canonical PI3K/AKT signaling axis to which SOX2 relates in various entangled, albeit not exclusive ways. Here we provide a comprehensive review of the current knowledge on SOX2 protein modifications, their proposed relationship to the PI3K/AKT pathway, and regulatory influence on SOX2 with regards to stemness, reprogramming, and cancer.